2021
DOI: 10.2196/28945
|View full text |Cite
|
Sign up to set email alerts
|

One Year of Pandemic Learning Response: Benefits of Massive Online Delivery of the World Health Organization’s Technical Guidance

Abstract: The World Health Organization (WHO) launched the first web-based learning course on COVID-19 on January 26, 2020, four days before the director general of the WHO declared a public health emergency of international concern. The WHO is expanding access to web-based learning for COVID-19 through its open-learning platform for health emergencies, OpenWHO. Throughout the pandemic, OpenWHO has continued to publish learning offerings based on the WHO’s emerging evidence-based knowledge for managing the COVID-19 pand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Learning effectiveness is presented based on twelve studies reported on effectiveness of digital learning, including all systematic reviews, which assessed online learning approaches in the areas listed below: technology-enabled knowledge translation strategies (TEKT) to increase use of research in public health [43]; digital education on chronic wound management [44]; artificial intelligence (AI), and diagnostic deep learning algorithms for medical imaging [45]; enablers, and barriers of e-learning in health sciences education [46]; cloud technology adoption in health sector [47]; digital education on clinical practice guidelines [48]; digital undergraduate education in dentistry [27]; and e-learning programmes in licensed health professionals [49]. Additionally, four quantitative, and one qualitative studies examined effectiveness of such digital activities: e-learning programme focusing on improving health care professionals' attitudes, and practices on breastfeeding [52]; e-learning course on child protection in medicine [53]; utilization of virtual worlds as a platform for collaborative meetings in health care [50]; and a massive online open course on implementation research for learners in low-and middle-income countries [9].…”
Section: Phase 1 Results: Overview Of the Examined Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Learning effectiveness is presented based on twelve studies reported on effectiveness of digital learning, including all systematic reviews, which assessed online learning approaches in the areas listed below: technology-enabled knowledge translation strategies (TEKT) to increase use of research in public health [43]; digital education on chronic wound management [44]; artificial intelligence (AI), and diagnostic deep learning algorithms for medical imaging [45]; enablers, and barriers of e-learning in health sciences education [46]; cloud technology adoption in health sector [47]; digital education on clinical practice guidelines [48]; digital undergraduate education in dentistry [27]; and e-learning programmes in licensed health professionals [49]. Additionally, four quantitative, and one qualitative studies examined effectiveness of such digital activities: e-learning programme focusing on improving health care professionals' attitudes, and practices on breastfeeding [52]; e-learning course on child protection in medicine [53]; utilization of virtual worlds as a platform for collaborative meetings in health care [50]; and a massive online open course on implementation research for learners in low-and middle-income countries [9].…”
Section: Phase 1 Results: Overview Of the Examined Literaturementioning
confidence: 99%
“…For example, most studies examined changes in the knowledge level of health professionals over time, yet study design varied from a cross-sectional with a pre-and post-test assessments (i.e. testing before and after learning activity) [53] to a longitudinal approach, where knowledge retention up to six months or a one-year follow up was carried out [52]. Consequently, these inconsistencies may lead to equivocal results demonstrated by authors.…”
Section: Phase 1 Results: Overview Of the Examined Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Many organizations replaced in-person training with online learning in response to restrictions on gathering and travel imposed during the COVID-19 pandemic. This shift required an expansion of online learning opportunities for HWs, which currently include massive open online courses (MOOCs) [ 14 ], webinars [ 15 ] and synchronous virtual communities of practice [ 16 ]. However, accessing, engaging with and learning in online environments can be challenging even under optimal circumstances.…”
Section: Introductionmentioning
confidence: 99%